Noel Rowe: Ethical Investigations: Essays on Australian Literature and Poetics edited by Bernadette Brennan (Journal of the Association for the Study of Australian Literature, 2010)
Noel Rowe: Ethical Investigations: Essays on Australian Literature and Poetics edited by Bernadette Brennan